The Selectivity of Ethanolic Extract of Buah Makassar (Brucea javanica) on Metastatic Breast Cancer Cells - Sutejo, Ika Rahmawati; Putri, Herwandhani; Meiyanto, Edy (Journal of Agromedicine and Medical Sciences, 2016)
Treatment of cancer such as surgery, radiotherapy and chemotherapy has many side effects. Chemopreventive agent is needed to reduce the side effect and increase the effectivity of therapy. The discovery of  cochemopreventive agent should consider on its selectivity to reduce side effects. The selective cochemopreventive agents work effectively in cancer cells and safe for normal cells. Buah Makassar (Brucea javanica) is a natural product that is empirically used for anti-inflammatory and antitumor. The purpose of this study is to determine the cytotoxic effect of ethanolic extract of buah Makassar against 4T1, MCF7, HeLa, and Vero cell lines. The cytotoxic test is performed by MTT assay. The parameter obtained from the cytotoxic test was IC50. Selectivity index is determined from IC50 ratio of cancer cells to normal cells. The results showed that ethanolic extract of buah Makassar has a cytotoxic activity on 4T1, MCF7, HeLa, and Vero cells with IC50 were 49,9±0,83 μg/mL; 107,6±8,14 μg/mL; 228,9±4,16 μg/mL and 395,5± 4,21 μg/mL respectively. It also has high selectivity on 4T1 metastatic breast cancer cell with selectivity index of 7,93. It can be concluded that the ethanolic extract of buah Makassar has potential to be delevoped as cochemopreventive agent especially on metastatic breast cancer. Keywords: Brucea javanica, MTT assay, selectivity index, 4T1, MCF7, HeLa, Vero